CAREER RECOMMENDER: A NOVEL APPROACH TO SUGGEST JOBS AND POST-GRADUATION STREAMS - Mathur, Prafful Nath; Dixit, Abhishek; Ramanathan, Sakkaravarthi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
To implement a novel approach to recommend jobs and colleges based on résumé of freshly graduated students. Job postings are crawled from webÂ using a web crawler and stored in a customized database. College lists are also retrieved for post-graduation streams and stored in a database. StudentÂ résumé is stored and parsed using natural language processing methods to form a résumé model. Text mining algorithms are applied on this modelÂ to extract useful information (i.e., degree, technical skills, extracurricular skills, current location, and hobbies). This information is used to suggestÂ matching jobs and colleges to the candidate. Â